Dampak COVID-19 Terhadap Hasil Analisis Kelayakan Investasi pada Saham Perusahaan BUMN - Susila, Muktar Redy (E-Jurnal Akuntansi, 2023)
The aim of the research is to analyze the impact of COVID-19 on the stock performance of State-Owned Enterprises (BUMN). The research sample is the shares of BUMN companies. The sampling technique used in this research is purposive sampling. The number of samples that met the research criteria were 19 state-owned companies. The method used to analyze the CAPM. The results of the analysis prior to COVID-19 found that five state-owned companies were efficient shares. The results of the analysis at the time of COVID-19 obtained that fifteen BUMN companies were efficient shares. The results of the different tests on the performance of BUMN shares before and during COVID-19 concluded that there were differences. The results of the study show that with COVID-19 the feasibility of state-owned company shares has changed. Keywords :  Stocks; COVID-19; CAPM; State-Owned Companies